Effectiveness of assessment techniques used in distance learning on undergraduates' academic performance: a conceptual model - Thathsarani, I.V.A.D.H.; Ariyananda, B.G.D.K.; Kaushalya, J.A.C.; Kerthiga, M.; Munasinghe, A.A.S.N.; Rathnayake, R.M.N.M. (University of Jaffna, 2022)
Purpose: With the rapid advancement of technology and the ongoing Covid-19 pandemic, all universities and higher academic institutes in Sri Lanka have adopted the distance-learning method to continue education since students and teachers cannot meet physically due to health guidelines and restrictions. The main purpose of this study is to understand the effectiveness of assessment techniques followed through distance learning in Sri Lankan undergraduates during Covid-19. Methodology: A comprehensive research strategy is used to collect the best research articles on this topic. Assessment of undergraduates' learning is a vital part, and academic achievement is based on a Grade Point Average (GPA), which is the most significant evaluation of students in university life. Findings: The findings of the study showed that the concept indicator model for online assessments in distance learning, consisting of online examinations, online presentations, online viva, and online quizzes were constructed. Implications: The findings of this study revealed that online assessment techniques may be useful in distance learning and further should be needed consideration by all universities and, different universities have adopted different types of online assessment techniques to evaluate undergraduates' performance in distance learning. Therefore, the concept paper concludes with a conceptual model that enables the testing of the effectiveness of assessment techniques used in distance learning on undergraduates' academic performance.
Keywords: Distance learning; Effectiveness of assessment techniques; Academic performance